A novel approach to field identification of cryptic Apodemus wood mice: calls differ more than morphology. (6th June 2016) - Ancillotto, Leonardo; Mori, Emiliano; Sozio, Giulia; Solano, Emanuela; Bertolino, Sandro; Russo, Danilo
Abstract: Field identification of European wood mice Apodemus spp. is challenging due to their morphological resemblance and frequent sympatry. We developed discriminant functions based on body mass and acoustic variables of distress calls to identify three cryptic species of wood mice ( Apodemus alpicola, Apodemus flavicollis and Apodemus sylvaticus ) in Italy. We achieved an overall correct classification rate of 86–98%; the best results (100% correct classification) were obtained for Apodemus sylvaticus calls. This minimally invasive, effective and low‐cost method highlights the potential role of bioacoustics as a powerful tool for field discrimination of cryptic species of terrestrial mammals.